The development of an integrated digital business platform as the realization of customer relationship management for student entrepreneurship at Polimedia - Kartika, Tipri Rose; Supiyanti , Tri Fajar Yurmama (Gema Wiralodra, 2024)
This research addresses the aforementioned challenge by proposing the Development of an Integrated Digital Business Platform as the Realization of Customer Relationship Management for Student Entrepreneurship at Polimedia. The methodology involves an in-depth analysis of existing entrepreneurship courses, business models, and current challenges faced by student-run ventures at Polimedia. A comparative study of successful integrated digital business platforms in educational institutions will also be conducted. Additionally, surveys, interviews, and focus group discussions will be utilized to gather insights from students, faculty, and stakeholders. The research will employ quantitative and qualitative approaches, ensuring a comprehensive understanding of the requirements and expectations. Explore existing literature on entrepreneurship education, digital business platforms, and Customer Relationship Management to establish a theoretical framework. The proposed Integrated Digital Business Platform is anticipated to provide an efficient and centralized solution for student businesses at Polimedia, fostering growth and visibility. By implementing Customer Relationship Management principles, the platform aims to enhance student engagement, increase market reach, and contribute to the overall success of student entrepreneurship initiatives at Polimedia.